Modern weapons and military equipment for issue 4-2018 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2018)
The Czar of battle: Russian artillery use in Ukraine portends advances;The M-91 Vihor Main Battle Tank: The Tank with Russian and American DNA